#TITLE_ALTERNATIVE# - Murni Wijaya (Nim: 10703076), Sri
Abstract: Recently, instant noodle producers increase their quality product by vitamins fortification. In this research, an analytical method applying high performance liquid chromatography technique (HPLC) for determination of water-soluble vitamins in instant noodle was developed. Prior the determination, the analytes were triturated using acetate buffer of pH 3.5 as extracting solvent and further purified by means of SPE method. An HPLC and solid phase extraction (SPE) method were developed to analyze water-soluble vitamins in instant noodle. An isocratic HPLC system under following conditions: methanol and 5 mM 1-hexanesulfonic acid solution in 1 percent aquaeous acetic acid solution adjusted to pH 3.5 with trietilamine (18.5:81.5) as eluting solvent, flow rate of 2 mL/min, as well as detection at 275 nm; were suitable for the determination of water soluble vitamins. Under this condition vitamin B1, B3, B6, and B11 gave limit of detection of 0.13, 0.26, 0.14, and 0.08 ppm; as well as limit of quantitation of 0.47, 0.86, 0.47, and 0.28 ppm, respectively. The precision of the determination of vitamin B1, B3, B6, and B11, stated as coefficient of variation (CV), were respectively 2.36, 0.38, 2.40, and 0.78 percent, while their accuracy stated as percentage of recovery, were respectively 82,73 - 89,18, 87,76 - 97,00, 87,71 - 96,69, and 242,41 - 440,07 percent. Generally, this method gave good precision and accuracy for determination vitamin B1, B3, and B6 in instant noodle.